Attitudes and Prescribing Practices of Community Pharmacists in the Accra Metropolis towards the Use of Misoprostol for Medical Abortion - Busia, N.T. (University of Ghana, 2016)
Background: Unsafe abortion is a significant public health problem. It accounts for 13% of maternal mortality worldwide and 11% in Ghana. Currently, Misoprostol is a drug used in the provision of medical abortion. Community pharmacies in Ghana are regularly the first port of call for most Ghanaians seeking healthcare advice or treatment, but little research has been done to assess community pharmacists‘ attitudes and prescribing practices regarding the use of misoprostol for medical abortion in Ghana. This research assessed the extent of availability and use of misoprostol for medical abortion at the community level. Method: A total of 165 community pharmacies were chosen at random from facilities within the Accra Metropolis. These facilities were chosen from different classes of residential areas within the Metropolis. Structured questionnaires were administered to the 165 community pharmacies chosen. This was complemented with mystery client surveys carried out in 100 of the community pharmacies. Descriptive, bivariate and logistic regression statistical analyses techniques were used to analyse and present the data. Results: Findings suggest that though Misoprostol was widely available at the community level its availability and demand did not differ significantly across the different residential areas. Majority of community pharmacists/pharmacy workers do not prescribe Misoprostol for medical abortion. Factors like age (p=0.225), religion (p=1.000), qualification (p=0.577) and knowledge of abortion legality (p=0.203) did not have significant effect on whether a pharmacy worker had ever dispensed Misoprostol to a client seeking abortion services or not. However, factors like sex (p<0.05), demand (p<0.001) and availability of misoprostol (p<0.001) had a significant effect. There were inconsistencies between the findings from the questionnaire and the mystery client approach as 22.0% respondents in the mystery client survey either said they had never given Misoprostol for abortion or denied having it in stock but offered it to the mystery client. Conclusion: From the findings of the study, it can be concluded that Misoprostol is widely available in the setting and it is fairly easy to obtain without a prescription. This suggests the need for interventions to ensure that misoprostol for medical abortion is not abused.
Thesis(MPH)-University of Ghana, 2016
Keywords: Prescribing Practices; Community Pharmacists; Misoprostol; Medical Abortion